Efektivitas Peraturan Perundang-Undangan Tentang Dana Desa Untuk Kemajuan Masyarakatnya - Indra Susanto; Ulya Kencana; Izomiddin Izomiddin (Universitas Batanghari Jambi, 2022)
In the political policy of the village, there has been a systematic uniformity through the laws and regulations. The enactment of the Law on Villages was followed by other regulations. With the enactment of Law No. 6/2014 on Villages, it has given new hope to build more independent villages. For example, 70 percent of village funds are allocated for development, and no more than 30 percent of other operations. Village funds are used by the village government based on the mandate of the law to be effective. This is in accordance with the goals and plans that have been set at the village meeting. For this reason, a study of the effectiveness of the legislation on village funds is very important. Based on the problems above, this study analyzes the effectiveness of the legislation on village funds on funding governance in villages for the advancement of rural communities. The research method used is juridical. Data analysis is described. In conclusion, the legislation on village funds is no longer effective, because it does not show the level of success that has been set, and the results of its activities are not in accordance with its objectives. Although it has been arranged, it is not yet perfect.